Eine saldenmechanische Perspektive auf die Schuldenbremse - Gunther Tichy (Wirtschaftsdienst, 2024)
The debt brake was introduced to limit electoral spending excesses and ensure (debt) sustainability. Although the debt ratio has been reduced, this has come at the cost of an investment backlog and persistent current account surpluses. The reason for this is the household savings surplus that cannot be utilised domestically. If these savings exceed the capital requirements of companies, either government debt or foreign debt inevitably increases. Consequently, the reduction in the debt ratio in recent years has led to higher foreign debt. In light of low interest rates, higher investments will benefit future generations more than lower debt levels.
Keywords: G51; H63; F21; 330